Robust HPLC-MS/MS quantification of N-acyl homoserine lactones (AHLs) in biomass-associated solid matrices reveals their aqueous–solid distribution in wastewater treatment systems - Xinhao Xu; Xuejun Bi; Hui Zhang; Boyan Xu; Xueqing Shi; Haifeng Zhang; Lihua Cheng; Xiaolin Zhou; Tang Yang; Kibaek Lee; Shujuan Huang; How Yong Ng (Water Research, 2026)

Employment of magnetic measurements for monitoring conversion reactions in Fe3O4 anodes for lithium and sodium ion batteries - Bi Fu; Minghan Yang; Junfu Cheng; Zhanxu Chen; Yunbao Zheng; Yifang Li; Guangqi Hu; Yingji He; Chengzhi Hu; Yaping Wang (Chemical Engineering Journal, 2026)

Self-powered vibration online monitoring of power transformers enabled by triboelectric nanogenerator - Qun Deng; Shijie Zhai; Xin Yu; Minghao Zhang; Daiyong Yang; Jingyao Luan; Wei Jiang; Xiangzhuang Bi; Hengyu Li; Tinghai Cheng (Chemical Engineering Journal, 2026)

Pollination niche overlap contributes to the maintenance of rare flowering species in alpine grasslands - Ting Yang; Cheng Bi; Gerardo Arceo-Gómez; Anton Pauw; Erliang Gao; Yuxian Wang; Zhigang Zhao (Oecologia, 2026)

Establishment of a Neonatal Facial Phenotype Atlas for Genetic Disease Screening in a Retrospective Chinese Cohort - Jieyi Chen; Yunqian Zhu; Bi Ze; Huihui Chen; Chuan Li; Qi Ni; Yulan Lu; Liyuan Hu; Lin Yang; Bingbing Wu; Huijun Wang; Laishuan Wang; et al. (Phenomics, 2026)

UAV coarse visual localization in large-scale continuous scenes - Cheng Bi; Jingfeng Wang; Zhengxi Li; Yang Zhao; Zhiyu Jiang; Yuan Yuan; Ganchao Liu (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Seven previously undescribed seco-abietane and seco-isopimarane type diterpenoids from Biscogniauxia sp. and their biological activities - Meng Zhang; Yang Yan; Wen-Song Bi; Liu-Yang Ma; Dan Hu; Liang-Dong Guo; Zuo-Cheng Qiu; Guo-Dong Chen; Huan Zhao; Hao Gao (Phytochemistry, 2026)

Low abundance microorganisms enhance soil multifunctionality by emphasizing fungal roles as mediated by plant biomass - Ze-Ying Zhao; Xiao-Bin Xiong; Peng-Yang Wang; Jia-Cheng Guo; Yinglong Chen; Hong-Yan Tao; Nan Chang; Cheng-Rui Bi; Yun-Lu Chen; Yuan Song; You-Cai Xiong (Applied Soil Ecology, 2026)

Spatially explicit process-resolved fluxes and microbial drivers: Linking community succession to greenhouse gas emissions from full-scale industrial wastewater treatment - Weiwei Kong; Rui Dai; Zhaohui Yang; Qinyang Li; Xin Cheng; Yuling Tang; Jianfei Zhou; Bi Shi (Journal of Water Process Engineering, 2026)

Metabolic Engineering of Selenocysteine Biosynthesis and Insertion Pathway in Lactococcus Lactis - Jing-Jing Peng; Yao Qin; Shi-Yang Yue; Ping Shi; Ling-Yu Wang; Chen-Xing Liu; Yu-Hui Fang; Xiao-Dong Pei; Fu-Tian Yu; Xin-Bi Huang; Xiao-Ling Liu; Cheng-Hua Wang (Biological Trace Element Research, 2026)

Dissolved and particulate phosphorus turnover in a river dominated marginal sea traced by cosmogenic 32P and 33P - Cheng Xu; Bin Yang; Jinlong Wang; Sheng Zeng; QianQian Bi; Jinzhou Du (Water Research, 2026)

An unprecedented alternariol-zinnol hybrid and six undescribed zinnol derivatives from the phytopathogen Alternaria solani and their cytotoxic activities - Ming Hu; Run-Cheng Yan; Qiao-Ling Wei; Jiang-Li Su; Bi-Juan Yang; Wen-Chao Tu; Gan-Peng Li; Xing-De Wu (Phytochemistry, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Enhancing anaerobic methane production from corn straw: Promoting lignocellulosic biomass biodegradation via aeration in liquid fraction of digestate for green and efficient pretreatment - Bi-Long Chen; Ting-Ting Zhang; Aqsa Arooj; Cheng Xu; Jia-Cheng E. Yang; Mika Sillanpää; Quan-Bao Zhao; Yu-Ming Zheng (Journal of Environmental Chemical Engineering, 2025)

Multi-omics profiling delineates reheating-modality-driven flavor divergence in Yuxiang shredded pork - Xuan Wang; Shaoran Shi; Xiaomeng Wu; Shuang Bi; Fan Yang; Xiuli Du; Youyou Cheng; Jingguang Li; Yunfeng Zhao; Dawei Chen (Food Chemistry, 2025)

Machine learning coupling microbial succession to decipher gas stripping-reinforced sulfate reduction for hydrogen sulfide removal - Ting-Ting Zhang; Ei Myat Mon Oo; Bi-Long Chen; Lin Liu; Quan-Bao Zhao; Jia-Cheng E. Yang; Yu-Ming Zheng (Bioresource Technology, 2025)

Empagliflozin attenuates sorafenib-promoted renal ferroptosis and inflammation by targeting cyclooxygenase-2/prostaglandin E2 axis - Ming-Kai Tsai; Wen-Chin Lee; Shih-Chung Huang; Chao-Cheng Huang; Yi-Chen Wang; Chien-Han Yuan; Chih-Chiang Wang; Ching-Han Liu; Nan-Chieh Huang; Yi-Chen Chang; Cheng-Chieh Fang; Bi-Wen Yeh; et al. (Toxicology and Applied Pharmacology, 2025)

Distribution, ozone formation potential, and health risk assessments of VOCs in automotive seat cushion leather during finishing process - Zhaohui Yang; Chuanhui Mu; Xin Cheng; Yuling Tang; Jianfei Zhou; Bi Shi (Journal of Hazardous Materials, 2025)

Sustainable and versatile bioplastics toward large-scale industrialization - Chunyu Wang; Yingying He; Yuan Wei; Yong Ye; Hongfu Bi; Cheng Zhang; Jie Ao; Tianning Yang; Feng Chen; Yangyang Qian; Yongjun Xu; Gang Chen (Chemical Engineering Journal, 2025)

Atrazine-induced hippocampal neurotoxicity: Involvement of Drp1-mediated mitochondrial fission - Jingran Yang; Ling Qi; Cheng Zhang; Ruirui Ding; Haoran Bi; Peng Li; Zhipeng Qi; Qiao Niu; Weiyi Song; Jianan Li (Chemico-Biological Interactions, 2025)

Hydroxyl-driven homogeneous and robust SAM anchoring on NiOx for high-performance inverted perovskite solar cells - Xiao Wu; Haoran Yang; Ziyao Yue; Yunfan Wang; Manting Liu; Jie Zeng; Leyu Bi; Qing-Dan Yang; Yanping Huo; Liming Ding; Alex K.-Y. Jen; Sai-Wing Tsang; et al. (Chemical Engineering Journal, 2025)

Associations of non-essential metal mixture with biological aging and the mediating role of inflammation in Chinese older adults - Yan Zhang; Yuan Wang; Xuqiu Cheng; Ziwei Tian; Yuantao Zhang; Wenyuan Liu; Xianglong Liu; Bing Hu; Fangbiao Tao; Anna Bi; Jun Wang; Linsheng Yang (Environmental Pollution, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Bayesian-based analysis of sequence activity characteristics in the Bohai Rim region - Jin-Meng Bi; Cheng Song; Fu-Yang Cao (Applied Geophysics, 2025)

High-strength, high-toughness, and high-barrier composite films based on bionic multi-scale fiber reinforcement and organic–inorganic interface hybridization for flexible food packaging - Cheng Zhang; Hongfu Bi; Yuan Wei; Yang Zhou; Chunyu Wang; Yingying He; Jie Ao; Shimin Kang; Gang Chen (Chemical Engineering Journal, 2025)

IsoVISoR: Towards 3D Mesoscale Brain Mapping of Large Mammals at Isotropic Sub-micron Resolution - Chao-Yu Yang; Yan Shen; Xiaoyang Qi; Lufeng Ding; Yanyang Xiao; Qingyuan Zhu; Hao Wang; Cheng Xu; Pak-Ming Lau; Pengcheng Zhou; Fang Xu; Guo-Qiang Bi (Neuroscience Bulletin, 2025)

A novel mutation in hERG gene associated with azithromycin-induced acquired long QT syndrome - Yun-Jiu Cheng; Yang Wu; Hui-Qiang Wei; Yi-Jian Liao; Li-Ping Qu; Yue-Han Pan; Li-Juan Liu; Wen-Tao Bi (Molecular Biology Reports, 2024)

Experimental species removal reveals species contributions to positive pollinator‐mediated reproductive interactions - Cheng Bi; Øystein H. Opedal; Ting Yang; Erliang Gao; Zhigang Zhao (Ecology, 2024)
Pollinator‐mediated reproductive interactions among co‐flowering plant species provide a canonical example of how biotic factors may contribute to species coexistence, yet we lack understanding of the exact mechanisms. Flowering‐dominant and unusually attractive “magnet species” with disproportionate contributions to pollination may play key roles in such reproductive interactions, but their relative roles within the same community have rarely been assessed. We experimentally removed either a flowering‐dominant or a highly attractive magnet species and compared effects on visitation frequency, pollinator richness, and seed set of co‐flowering plants. Removal of either the flowering‐dominant species or the magnet species reduced community‐level pollinator visitation. Removal of the magnet species had the most consistent effect, including reduced pollinator visitation and richness, and reduced seed set of most co‐flowering plants. These results suggest that the magnet species, which interacts with a wider range of pollinator species than does the dominant species, promotes the visitation and reproductive fitness of most other species. Removal of the flowering‐dominant species affected only certain species, perhaps because these plants had floral traits similar to the dominant species. Our results highlight the role of attractive magnet species within a community in structuring reproductive interactions and identify potential mechanisms involved in coexistence facilitated by reproductive interactions.

The relationship between maternal environmental temperature exposure and preterm birth: A Risk prediction based on machine learning - Yuxiao Wang; Xing Bi; Yang Cheng; Yingjie Du; Ling Feng; Shaoshuai Wang (Sustainable Cities and Society, 2024)

Predictive modeling of patulin accumulation in apple lesions infected by Penicillium expansum using machine learning - Xiaoyan Cheng; Rongxia Li; Pengdong Xie; Xuexue Wang; Lirong Yu; Ruofei Wu; Huali Xue; Yang Bi (Postharvest Biology and Technology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Identification ATP5F1D as a Biomarker Linked to Diagnosis, Prognosis, and Immune Infiltration in Endometrial Cancer Based on Data-Independent Acquisition (DIA) Analysis - Yuemei Cheng; Xiaolei Liang; Xuehan Bi; Chang Liu; Yongxiu Yang (Biochemical Genetics, 2024)

Correction: Experimental grazer exclusion increases pollination reliability and influences pollinator-mediated plant-plant interactions in Tibetan alpine meadows - Cheng Bi; Øystein H. Opedal; Ting Yang; Lili Yang; Erliang Gao; Meng Hou; Zhigang Zhao (Alpine Botany, 2024)

Alleviation of RO membrane fouling in wastewater reclamation plants using an enhanced acid-base chemical cleaning method - Li Zihao; Jinlong Wang; Lihua Cheng; Qiang Yang; Peizhuo Li; Xiaowan Dong; Boyan Xu; Mei Zhi; Anni Hao; How yong Ng; Xuejun Bi (Water Research, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Intensive coagulation of secondary effluent to mitigate reverse osmosis membrane fouling at low temperatures: Strategies of pre-oxidation and coagulant aids addition - Qiang Yang; Xiaohan Wei; Tengfei Hu; Jie Wang; Peizhuo Li; Aili Gao; Jinlong Wang; Lihua Cheng; Shujuan Huang; Xuejun Bi (Journal of Water Process Engineering, 2024)

Wearable solid-phase microextraction sampling for enhanced detection of volatile analytes in human ears - Wenzheng Mo; Lei Li; Bi-Cheng Yang; Xiangjie Wang; Baixue Wang; Jianfeng Zhang; Qiaoyun Huang; Zhong-Ping Yao; Dong Zhang; Bin Hu (Analytica Chimica Acta, 2024)

Effectiveness of a novel compound microbial agent for water quality and the gut microbiota of Micropterus salmoides - Qian Li; Li-Hui Sun; Bi-Cheng Yang; Jian-Hu Jiang; Jian-Ming Chen; Gang Zheng; Ling-Mei Gao; Jun Peng; Jian-Lin Guo (Frontiers in Marine Science, 2024)
The cultivation of largemouth bass ( Micropterus salmoides ), a species of significant economic value in aquaculture, has experienced notable growth recently. However, the deterioration of water quality seriously affects the metabolic responses of M. salmoides . While compound microbial agent (CMA) is widely utilized for ecological rehabilitation and water filtration, its application in M. salmoides has not been reported. Here, based on physio-biochemical tests and 16S rRNA sequencing, we investigated the effects of CMA (yeast, Bacillus subtilis , and lactic acid bacteria) on the water quality within the recirculating aquaculture system, along with physiological indices and gut microbiota of M. salmoides . Compared to the control and single microbial agent (yeast), CMA treatment improved the water quality by improving the dissolved oxygen and delaying the increase of pH, total nitrogen, total phosphorus, ammonia nitrogen, and nitrite. The 16s rRNA gene sequencing revealed that the water treated with CMA exhibited elevated levels of chao1, Shannon, Pd, and a larger population of dominant bacterial. Besides, higher values of ACE, chao1, Shannon, and OTU level, and lower Simpson index were found in CMA treated M. salmoides samples, suggesting that CMA treatment enhanced the species richness and diversity of gut microbiota of M. salmoides . Furthermore, CMA treatment hindered the generation and proliferation of harmful bacteria, such as the Mycoplasma mobile 163K species and the Erysipelotrichaceae family, which was associated with enhanced antioxidant enzymatic activity and decreased MDA level in both the serum and liver. These findings shed light on the essential roles of CMA in M. salmoides culturing and introduce an innovative approach to enhance the aquatic environment.

Experimental grazer exclusion increases pollination reliability and influences pollinator-mediated plant-plant interactions in tibetan alpine meadows - Cheng Bi; Øystein H. Opedal; Ting Yang; Lili Yang; Erliang Gao; Meng Hou; Zhigang Zhao (Alpine Botany, 2024)

Performance and mechanism of sequential UV-NaClO disinfection: Inactivation and reactivation of antibiotic-resistant bacteria, disinfection byproduct formation and microbial community variation - Lihua Cheng; Xiaohan Wei; Aili Gao; Lin Zhou; Xueqing Shi; Xiaolin Zhou; Xuejun Bi; Tang Yang; Shujuan Huang (Journal of Water Process Engineering, 2024)

Exploring ANFIS application based on actual data from wastewater treatment plant for predicting effluent removal quality of selected major pollutants - Liang Qiao; Pei Yang; Qi Leng; Liujie Xu; Yanxin Bi; Jinzhen Xu; Zhe Wang; Jianye Liu; Wanxin Yin; Luyan Zhang; Feihong Wang; Ye Yuan; et al. (Journal of Water Process Engineering, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Preparation of P-doped biochar and its high-efficient removal of sulfamethoxazole from water: Adsorption mechanism, fixed-bed column and DFT study - Yizhen Cheng; Jingrui Yang; Jimin Shen; Pengwei Yan; Shan Liu; Jing Kang; Lanbo Bi; Binyuan Wang; Shengxin Zhao; Zhonglin Chen (Chemical Engineering Journal, 2023)

The influence of MPL addition on structure, interfacial compositions and physicochemical properties on infant formula fat globules - Yibo Liu; Lu Liu; Shuming Liu; Meng Sun; Yang Jiao; Jing Chai; Lianji Bi; Awa Fanny Massounga Bora; Xiaodong Li; Xiuxiu Zhang; Bincheng Liu; Jinju Cheng; et al. (Food Research International, 2023)

Quercetin alleviates tubulointerstitial inflammation by inhibiting exosomes-mediated crosstalk between tubular epithelial cells and macrophages - Di Yin; Jing-Yuan Cao; Yan Yang; Zhong-Tang Li; Hong Liu; Tao-Tao Tang; Wei-Jie Ni; Yi-Lin Zhang; Wei Jiang; Yi Wen; Zuo-Lin Li; Jing Zhao; et al. (Inflammation Research, 2023)

Performance characteristics and bacterial community analysis of a novel two-step-feed three-stage A/O-MBBR system for nitrogen removal in municipal wastewater - Xiaolin Zhou; Zijian Jiang; Jinzhao Gu; Xuejun Bi; Jingmiao Liu; Xuyi Wang; Tang Yang; Xueqing Shi; Lihua Cheng; Shujuan Huang; Xiaodong Wang; Harsha Ratnaweera; et al. (Journal of Water Process Engineering, 2023)

Cytotoxic steroidal glycosides from the rhizomes of Paris polyphylla var. yunnanensis - Yang Liu; Mei-You Liu; Lin-Lin Bi; Yun-Yuan Tian; Peng-Cheng Qiu; Xiao-Ying Qian; Min-Chang Wang; Hai-Feng Tang; Yun-Yang Lu; Bang-Le Zhang (Phytochemistry, 2023)

Simultaneous determination of dissolved organic nitrogen, nitrite, nitrate and ammonia using size exclusion chromatography coupled with nitrogen detector - Wen-Xiang Ji; Ye-Chao Tian; Min-Hui Cai; Bi-Cun Jiang; Shi Cheng; Yan Li; Qing Zhou; Bo-Qiang Li; Bai-Yang Chen; Xing Zheng; Wen-Tao Li; Ai-Min Li (Journal of Environmental Sciences, 2023)

Fouling characteristic of reverse osmosis membrane for reclaimed water treatment operating under cold winter condition - Zi-Hao Li; Guo-Wei Ni; Jin-Long Wang; Lin Zhou; Qiang Yang; Pei-Zhuo Li; Ai-Li Gao; Tong Yu; Li-Hua Cheng; Xue-Jun Bi (Desalination, 2023)

Activity characteristics of significant earthquake swarms in the Bohai Rim region - Jin-Meng Bi; Cheng Song; Fu-Yang Cao (Applied Geophysics, 2023)

Synthesis of crown ether-based microporous organic networks: A new type of efficient adsorbents for chlorophenols - Yi-Xuan Wang; Yan-Ping Bi; Yuan-Yuan Cui; Cheng-Xiong Yang (Journal of Hazardous Materials, 2023)

A flexible zinc ion hybrid capacitor integrated system with layers-dependent V2CTx MXene - Sairao Zhao; Xiao Luo; Yongfa Cheng; Zhixiang Shi; Tao Huang; Shanghua Yang; Haojian Zheng; Yun Bi; Jun Zhang; Qiuyue Shi; Minglei Cao; Chuankun Zhang; et al. (Chemical Engineering Journal, 2023)

Artificial intelligence technologies in bioprocess: Opportunities and challenges - Yang Cheng; Xinyu Bi; Yameng Xu; Yanfeng Liu; Jianghua Li; Guocheng Du; Xueqin Lv; Long Liu (Bioresource Technology, 2023)

Programmable phthalocyanine-iron-based nanoreactor for fluorescence/magnetic resonance dual-modality imaging-guided sono/chemodynamic therapies - Dong Li; Jie Pan; Shuyu Xu; Bingwei Cheng; Shuaiying Wu; Qixuan Dai; Mei-Rong Ke; Bi-Yuan Zheng; Chengchao Chu; Chao Liu; Yang Zhang; Xiao Xu; et al. (Chemical Engineering Journal, 2023)

Migration and abiotic transformation of estrone (E1) and estrone-3-sulfate (E1-3S) during soil column transport - Banghao Du; Weiwei Yu; Lun Yang; Gongduan Fan; Shuo Yang; Hui Jiang; Shenglan Bi; Cheng Yu (Environmental Geochemistry and Health, 2022)

Detection and significance of exosomal mRNA expression profiles in the cerebrospinal fluid of patients with meningeal carcinomatosis - Peng Cheng; Feifei Feng; Hui Yang; Suqin Jin; Chao Lai; Yun Wang; Jianzhong Bi (Journal of Molecular Neuroscience, 2021)

Pseudomonas laoshanensis sp. nov., isolated from peanut field soil - Ming-Qing Wang; Chu-Shu Zhang; Li-Na Yu; Wei-Qiang Yang; Kun Jiao; Kui-Jie Gong; Xiao-Yuan Chi; Jie Bi; Yu Song; Qing-Li Yang; Jian-Cheng Zhang; Gui-Wen Yang; et al. (Archives of Microbiology, 2021)

Optimization of the protoplast transient expression system for gene functional studies in strawberry (Fragaria vesca) - Yi-Jie Gou; Yu-Lian Li; Pin-Pin Bi; Dan-Juan Wang; Yang-Yang Ma; Yang Hu; Hou-Cheng Zhou; Ying-Qiang Wen; Jia-Yue Feng (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

The application of the ‘Gene-deletor’ technology in banana - Chun-hua Hu; Qiao-song Yang; Xiu-hong Shao; Tao Dong; Fang-cheng Bi; Chun-yu Li; Gui-ming Deng; Yi Li; Gan-jun Yi; Tong-xin Dou (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Banana ( Musa spp.) is an important tropical crop. Banana industry is under biotic and abiotic stresses such as Fusarium wilt, typhoon, cold stress. Genetic engineering offers a powerful strategy to create germplasm of banana with enhanced resistance. The safety of genetically modified organisms has become a bottleneck restricting the popularization and application of genetically modified technology. In this study, a candidate promoter, LEAFY (LFY) for expression and flower initiation in Arabidopsis , was cloned and constructed to ‘Gene-deletor’ vector. Histochemical β-glucuronidase (GUS) staining results showed that the ‘Gene-deletor’ vector driven by LFY promoter could lead to 88.5% excision efficiency from Arabidopsis seeds based on more than 200 T 3 progeny examined per event. GUS staining was found to be partially negative in transgenic bananas, however, polymerase chain reaction could still detect the presence of large fragments of the vector. These results suggest that although LFY promoter could not completely drive the ‘Gene-deletor’ vector to achieve the effect of complete elimination of exogenous gene in bananas, its efficiency of eliminating exogenous gene laid a theoretical foundation for cloning banana fruit-specific promoters, that is, ‘non-transgenic’ GM bananas.

Fine mapping, candidate genes analysis, and characterization of a brown planthopper (Nilaparvata lugens Stål) resistance gene in the rice variety ARC5984 - Jiebin Lin; Xinyi Wang; Yang Li; Fanggui Bi; Ling Cheng; Fengkuang Huang; Rongbai Li; Yongfu Qiu (Euphytica, 2020)

Genomic characterizations of H4 subtype avian influenza viruses from live poultry markets in Sichuan province of China, 2014–2015 - Chuansong Quan; Ting Huang; Xiuwei Chen; Jie Zhang; Qianli Wang; Cheng Zhang; Tiyan Zhang; Lijun Zhou; Liumei Shu; Chunrong Long; Lei Yang; Xunbo Du; et al. (Science China Life Sciences, 2018)

Biglycan, a Nitric Oxide-Downregulated Proteoglycan, Prevents Nitric Oxide-Induced Neuronal Cell Apoptosis via Targeting Erk1/2 and p38 Signaling Pathways - Sujuan Chen; Dandan Guo; Wei Zhang; Yunfei Xie; Haijie Yang; Binfeng Cheng; Lei Wang; Rui Yang; Jiajia Bi; Zhiwei Feng (Journal of Molecular Neuroscience, 2018)

NCAM affects directional lamellipodia formation of BMSCs via β1 integrin signal-mediated cofilin activity - Jia-Jia Bi; Jing Li; Bin-Feng Cheng; Hai-Jie Yang; Qiong-Qiong Ding; Rui-Fei Wang; Su-Juan Chen; Zhi-Wei Feng (Molecular and Cellular Biochemistry, 2017)

Infralimbic Endothelin1 Is Critical for the Modulation of Anxiety-Like Behaviors - Lin-Lin Bi; Ming Chen; Lei Pei; Shu Shu; Hui-Juan Jin; Hong-Lin Yan; Na Wei; Shan Wang; Xin Yang; Huan-Huan Yan; Meng-meng Xu; Cheng-Ye Yao; et al. (Molecular Neurobiology, 2016)

Intranasal Delivery of Granulocyte Colony-Stimulating Factor Enhances Its Neuroprotective Effects Against Ischemic Brain Injury in Rats - Bao-liang Sun; Mei-qing He; Xiang-yu Han; Jing-yi Sun; Ming-feng Yang; Hui Yuan; Cun-dong Fan; Shuai Zhang; Lei-lei Mao; Da-wei Li; Zong-yong Zhang; Cheng-bi Zheng; et al. (Molecular Neurobiology, 2016)

miR-137 suppresses the invasion and procedure of EMT of human breast cancer cell line MCF-7 through targeting CtBP1 - Yong Han; Yueyang Bi; Haiyang Bi; Caimei Diao; Guoqiang Zhang; Kai Cheng; Zhenlin Yang (Human Cell, 2016)

RETRACTED ARTICLE: Relationship of Serum Heart-Type Fatty Acid-Binding Protein Levels and Cerebral Infarction: a Meta-analysis - Bao-Liang Sun; Ming-Feng Yang; Xiao-Yi Yang; Jing-Yi Sun; Da-Wei Li; Zong-Yong Zhang; Lei-Lei Mao; Cun-Dong Fan; Cheng-Bi Zheng; Hong-Li Gao; Feng-Ze Wang; Feng Zhang; et al. (Molecular Neurobiology, 2015)

Satellite-Based Investigation and Evaluation of the Observational Environment of Meteorological Stations in Anhui Province, China - Yu-Bin Li; Tao Shi; Yuan-Jian Yang; Bi-Wen Wu; La-Bao Wang; Chun-E Shi; Jian-Xia Guo; Cheng-Li Ji; Hua-Yang Wen (Pure and Applied Geophysics, 2015)

Enrichment of cardiac differentiation by a large starting number of embryonic stem cells in embryoid bodies is mediated by the Wnt11-JNK pathway - Ming Chen; Cheng Qian; Lin-Lin Bi; Fang Zhao; Guang-Yu Zhang; Zhi-Quan Wang; Xue-Dong Gan; Yang-Gan Wang (Biotechnology Letters, 2015)

Identification and expression analysis of four 14-3-3 genes during fruit ripening in banana (Musa acuminata L. AAA group, cv. Brazilian) - Mei-Ying Li; Bi-Yu Xu; Ju-Hua Liu; Xiao-Liang Yang; Jian-Bin Zhang; Cai-Hong Jia; Li-Cheng Ren; Zhi-Qiang Jin (Plant Cell Reports, 2012)

Comparative temporal analyses of the Pinus sylvestris L. var. mongolica litv. apical bud proteome from dormancy to growth - Ying-Dong Bi; Zhi-Gang Wei; Zhuo Shen; Tian-Cong Lu; Yu-Xiang Cheng; Bai-Chen Wang; Chuan-Ping Yang (Molecular Biology Reports, 2011)

Establishment and characterization of a new highly metastatic human osteosarcoma cell line - Yuxi Su; Xiaoji Luo; Bai-Cheng He; Yi Wang; Liang Chen; Guo-Wei Zuo; Bo Liu; Yang Bi; Jiayi Huang; Gao-Hui Zhu; Yun He; Quan Kang; et al. (Clinical & Experimental Metastasis, 2009)